Implementasi Pembelajaran Sistem Among di SMK Taman Karya Madya Teknik Kebumen - Mulyanto Mulyanto; R Rejokirono; Joko Purwanto (Universitas Sarjanawiyata Tamansiswa, 2021)
The aims of this study were 1) to analyze the learning model used at vocational high school taman karya madya teknik kebumen. 2) to analyze the extent to which the among sistem learning model has been implemented in vocational high school taman karya madya teknik kebumen. 3) To analyze the supporting factors and inhibiting factors for the implementation of the among sistem learning model at vocational high school Taman Karya Madya Teknik Kebumen. The type of research was case study, qualitative approach with stages of data collection, data reduction, data presentation and conclusion drawing. The results of the study showed that (1) the learning model used in vocational high school taman karya madya teknik kebumen was a combination of the among sistem with inquiry learning, discovery learning, project based learning, and problem based learning. (2) Among sistem learning model was applied starting from the following components: study program selection, teaching and learning process, talent and interest development, and learning evaluation. (3) The supporting factor for implementing the Among sistem learning was that all educators and education staff have been living the teachings of tamansiswa so that there were no obstacles in implementing the among sistem.